(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2022)
A recent play by Alberto Conejero, La geometría del trigo (first edition: 2018; first staging: 2019), is thoroughly analyzed in its complex temporal structure, and a depiction of its social and geographical backgrounds is offered. The study reviews the relationships between the six characters and identifies the unbreakable bond between generations as the thematic core of the play.